Key factors affecting Fe density in Fe-fortified-parboiled rice: Parboiling conditions, storage duration, external Fe-loading rate and genotypic differences - Chanakan Prom-u-thai (2018)
The present study evaluated the key factors affecting the efficiency of iron (Fe) penetration into the endosperm in parboiled rice of different varieties. It also investigated effects of storage time on Fe bio-accessibility, rice colour and Fe retention after rinsing. Rice grains of three varieties were fortified with an increasing range of Fe-fortification rates during the parboiling process, under two typical parboiling conditions, which are ambient soaking temperature for 24h and 60°C soaking temperature for 6h at neutral (6.0-6.5) and acidic pH (3.0-3.5). Soaking of paddy rice, at 60°C in acidic water for 6h before steaming, was found to be better for maximising the Fe concentration in white-parboiled rice than the former ambient soaking. Under this parboiling condition, adding 250mgFekg-1of paddy rice, at soaking, produced the most desirable Fe concentration in white rice, ranging from 17.5 to 25.4mgkg-1among the rice varieties tested. The concentrations of Fe in parboiled white rice exhibited an exponential increase with increasing concentrations of Fe in the soaking water in all varieties, which were linearly related to Fe concentration of brown rice (r=0.96**, p<0.01). The colour of the parboiled rice fortified with Fe was initially light yellow, with variation among rice varieties, but it did become slightly darker after 16weeks of storage, probably because of Fe oxidisation. This may be related to decreasing bio-accessibility after 20weeks of storage. Storage, however, did not affect the total Fe retention after rinsing, though the retention rate was variety-dependent. Information about parboiling will provide the basis for formulating an optimal industry protocol for producing Fe-fortified-parboiled rice, which can be further refined in pilot studies on the industrial scale. © 2010 Elsevier Ltd.